Meat tenderness: Physical and biochemical facts related to agricultural and industrial process. - Chacón Villalobos, Alejandro (2004)
Nowadays,the problem of meat tenderness is of great concern amongproducers because this parameter has become the mostimportant criteria upon which consumers judge meat quality.This problem is especially critical when it is also a provenfact that one of every four sensorial experiences of theconsumer is unsatisfactory when eating meat. This paperoverviews the main aspects determining meat tendernesssuch has structural and chemical composition of meat,muscular contraction, biochemical postmortem changes(rigor mortis and meant aging) and the general effects causedby industrial processing when cooking and freezing. Generalmethods for improving meat tenderness and the biochemicalactivity of the calcium ion dependent papain like cisteineproteases (CALPAIN) are also reviewed.